Lumasiran for primary hyperoxaluria type 1: What we have learned? - Gang, Xuan; Liu, Fei; Mao, Jianhua (Frontiers in Pediatrics, 2023)
Primary hyperoxaluria type 1 (PH1) is a rare autosomal recessive genetic disorder caused by mutations in the AGXT gene. The hepatic peroxisomal enzyme alanine glyoxylate aminotransferase (AGT) defects encoded by the AGXT gene increase oxalate production, resulting in nephrocalcinosis, nephrolithiasis, chronic kidney disease, and kidney failure. Traditional pharmacological treatments for PH1 are limited. At present, the treatment direction of PH1 is mainly targeted therapy. Lumasiran (OxlumoTM, developed by Alnylam Pharmaceuticals), an investigational RNA interference (RNAi) therapeutic agent, is the first drug approved for the treatment of PH1, which was officially approved by the US Food and Drug Administration and the European Union in November 2020. It is also the only drug that has been shown to decrease harmful oxalate. Currently, there are 5 keys completed and ongoing clinical trials of lumasiran in PH1. Through the three phase III trials that completed the primary analysis period, lumasiran has been shown to be effective in reducing oxalate levels in urine and plasma in different age groups, such as children, adults, and patients with advanced kidney disease, including those on hemodialysis. In addition to clinical trials, cases of lumasiran treatment for PH1 have been reported in small infants, twin infants, and children diagnosed with PH1 after kidney transplantation. These reports confirm the effectiveness and safety of lumasiran. All adverse events were of mild to moderate severity, with the most common being mild, transient injection-site reactions. No deaths or severe adverse events were reported. This article reviews PH1 and lumasiran which is the only approved therapeutic drug and provide new options and hope for the treatment of PH1.